Psychological Distress and Protective Behaviors During the COVID-19 Pandemic Among Different Populations: Hong Kong General Population, Taiwan Healthcare Workers, and Taiwan Outpatients - Chung, Gary Ka-Ki; Strong, Carol; Chan, Yat-Hang; Chung, Roger Yat-Nork; Chen, Jung-Sheng; Lin, Yi-Hsuan; Huang, Ru-Yi; Lin, Chung-Ying; Ko, Nai-Ying (Frontiers in Medicine, 2022)
Purpose The novel coronavirus disease 2019 (COVID-19) caused psychological distress and changed human living styles. However, rare studies have examined the psychological distress and protective behaviors across different populations. Therefore, the present study aimed to assess psychological distress, protective behaviors, and potential predictors of psychological distress and protective behaviors across the Hong Kong general population, Taiwan healthcare workers, and Taiwan outpatients. Methods A cross-sectional design was used to recruit participants from Hong Kong and Taiwan. Telephone interviews were carried out for Hong Kong participants (n = 1,067; 30.2% male participants); online surveys were used for Taiwan healthcare workers (n = 500; 8.0% male participants) and Taiwan outpatients (n = 192; 32.8% male participants). All the participants completed questions on psychological distress and protective behaviors. Multiple linear regressions and multivariable logistic regressions were employed to explore the potential predictors of psychological distress and protective behaviors, respectively. Results Hong Kong participants had significantly lower levels of psychological distress than Taiwan participants [mean (SD) = 0.16 (0.39) vs. 0.47 (0.59) in healthcare workers and 0.46 (0.65) in outpatients; p < 0.001]. Hong Kong participants (51.7%) and Taiwan outpatients had more people showing fear of COVID-19 (52.0%) than Taiwan healthcare providers (40.8%; p < 0.001). Moreover, Hong Kong participants engaged the most in protective behaviors, followed by Taiwan healthcare providers and Taiwan outpatients (p < 0.001). Moreover, being a female, fear of COVID-19 and worry about personal savings were associated with protective behaviors in general. Conclusions Despite the greater COVID-19 severity and fear of COVID-19 in Hong Kong, the general population in Hong Kong experienced less psychosocial distress with higher compliance to protective behaviors than the other groups in Taiwan.